STUDI EFEKTIVITAS PENGADAAN BARANG DAN JASA PEMERINTAH SECARA TRADISIONAL DAN ELEKTRONIK - Tanesia, Randy Kristovand (Jurnal Teknik Sipil, 2018)
Abstract: During the procurement of goods and services is done in two method online and traditional where the traditional method of using fax and telephone as a media. Two method are not going well because it is considered to have some weaknesses that could hurt the company such as the lack of accurate reports on the stock of products, distribution and product delivery and scheduling product delivery, the ineffectiveness of the work because it uses different media, and lack of transparency. In an effort to compensate for the shortcomings and difficulties in the procurement of goods and services and to create the procurement of goods and services that are transparent and clean should be utilized in the integration of information technology development process of procurement of goods and services, one of which is the E-Procurement. So in this study the authors aimed to distinguish the effectiveness of the procurement of goods and services traditionally and electronically from the aspect of cost, time and satisfaction and to identify the effectiveness of government procurement electronically in eliminating mode can block the development of the use of government budget. From research conducted shows that when viewed from the aspect of cost, time and satisfaction there is no relationship between the procurement of goods and services traditionally and electronically, and the difference between the procurement of goods and services traditionally and electronically. And it can be concluded that the effectiveness of the procurement of goods and services electronically has a moderate level of effectiveness in eliminating mode that can block the development of the use of the government budget.Â Abstrak: Selama ini pengadaan barang dan jasa dilakukan dengan dua cara yaitu secara online dan secara tradisional dimana cara tradisional ini menggunakan fax dan telepon sebagai medianya. Dua cara ini tidak berjalan baik karena dinilai memiliki beberapa kelemahan yang dapat merugikan perusahaan seperti kurangnya akuratnya laporan mengenai stok produk, distribusi pengiriman produk serta penjadwalan pengiriman produk, tidak efektifnya pekerjaan karena menggunakan media yang berbeda - beda, serta kurangnya transparansi. Dalam usaha untuk menutup kelemahan - kelemahan dan kesulitan dalam proses pengadaan barang/jasa dan untuk menciptakan pengadaan barang/jasa yang transparan dan bersih perlu dimanfaatkan perkembangan teknologi informasi dalam integrasi proses pengadaan barang/jasa tersebut, salah satunya adalah E-Procurement. Sehingga pada penelitian ini penulis bertujuan untuk membedakan efektivitas pengadaan barang dan jasa secara tradisional dan secara elektronik dari aspek biaya, waktu dan kepuasan serta mengidentifikasi efektivitas pengadaan pemerintah secara elektronik dalam mengeliminir modus yang dapat menghadang perkembangan penggunaan anggaran pemerintahan. Dari penelitian yang dilakukan menunjukkan bahwa bila ditinjau dari aspek biaya, waktu dan kepuasan tidak ada hubungan antara pengadaan barang dan jasa secara tradisional dan secara elektronik dan adanya perbedaan antara pengadaan barang dan jasa secara tradisional dan secara elektronik. Dan dapat disimpulkan bahwa efektivitas pengadaan barang dan jasa secara elektronik memiliki tingkat efektivitas sedang dalam mengeliminir modus yang dapat menghadang perkembangan penggunaan anggaran pemerintah.